2021
DOI: 10.1002/cncr.33870
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pegylated arginine deiminase and modified FOLFOX6 in patients with advanced hepatocellular carcinoma: Results of an international, single‐arm, phase 2 study

Abstract: BACKGROUND: Arginine starvation depletes the micronutrients required for DNA synthesis and interferes with both thymidylate synthetase activity and DNA repair pathways in preclinical models of hepatocellular carcinoma (HCC). Pegylated arginine deiminase (ADI-PEG 20), an arginine degrader, potentiates the cytotoxic activity of platinum and pyrimidine antimetabolites in HCC cellular and murine models. METHODS: This was a global, multicenter, open-label, single-arm, phase 2 trial of ADI-PEG 20 and modified 5-fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, a phase III study did not show a significant difference in overall survival or progression-free survival between ADI-PEG 20 and placebo [ 103 ]. Another phase II study found ADI-PEG 20 to be safe and effective in stabilizing the progression of heavily pretreated advanced HCC in an Asian population, while a study evaluating the combination of ADI-PEG 20 and modified 5-fluorouracil, leucovorin, and oxaliplatin (mFOLFOX6) in patients with advanced HCC who had progressed on at least two prior lines of treatment exhibited limited antitumor activity [ 104 ].…”
Section: Enzyme-mediated Arginine Deprivation Agents For Cancer Thera...mentioning
confidence: 99%
“…However, a phase III study did not show a significant difference in overall survival or progression-free survival between ADI-PEG 20 and placebo [ 103 ]. Another phase II study found ADI-PEG 20 to be safe and effective in stabilizing the progression of heavily pretreated advanced HCC in an Asian population, while a study evaluating the combination of ADI-PEG 20 and modified 5-fluorouracil, leucovorin, and oxaliplatin (mFOLFOX6) in patients with advanced HCC who had progressed on at least two prior lines of treatment exhibited limited antitumor activity [ 104 ].…”
Section: Enzyme-mediated Arginine Deprivation Agents For Cancer Thera...mentioning
confidence: 99%
“…This strategy is a desirable option because cancer cells frequently alter their metabolic and nutrient acquisition pathways to overcome numerous tumour microenvironmental stresses that threaten their survival and ability to proliferate [ 4 ]. Arginine, a semi-essential amino acid, is involved in numerous metabolic pathways [ 5 , 6 ] and arginine deprivation has been used to treat cancer in clinical trials [ 7 , 8 ] like normal cells which can de novo synthesise arginine, frequent deregulation of argininosuccinate synthase 1 (ASS1) in TNBC makes these cancer cells highly dependent on the uptake of extracellular arginine [ 9 ]. This arginine-auxotrophic phenotype is commonly seen in the metabolic reprogramming of cancer cells [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The encouraging results of two phase III studies conducted by Qin et al 13 and Lyn et al 14 revealed that FOLFOX4 (oxaliplatin +5-fluorouracil/leucovorin) may confer some benefits to advanced HCC patients in Asia, with an acceptable safety profile. Although the FOLFOX4 regimen has gained approval for the treatment of advanced HCC in China and has served as an empiric treatment option by some physicians in the United States, [15][16][17] it must be acknowledged that the benefits that advanced HCC patients receive from current chemotherapy regimens are still very limited, and the incidence of AEs is also relatively high. Additionally, we consider that the prognosis of advanced HCC patients is highly heterogeneous and needs to be reclassified for treatment.…”
Section: Introductionmentioning
confidence: 99%